Effects of soaking time and freezing on the gel strength of Moi-Moi prepared from Cowpea grains - Ikechukwu Otuosorochi Amagwula; Chijioke M. Osuji; Chinenyenwa Gloria Omeire; Umama Yezdani; Mohammad Gayoor Khan; Chinaza Godswill Awuchi (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.